2012
DOI: 10.1021/jm3001289
|View full text |Cite
|
Sign up to set email alerts
|

Rational Evolution of a Novel Type of Potent and Selective Proviral Integration Site in Moloney Murine Leukemia Virus Kinase 1 (PIM1) Inhibitor from a Screening-Hit Compound

Abstract: Serine/threonine kinase PIM1 is an emerging therapeutic target for hematopoietic and prostate cancer therapy. To develop a novel PIM1 inhibitor, we focused on 1, a metabolically labile, nonselective kinase inhibitor discovered in our previous screening study. We adopted a rational optimization strategy based mainly on structural information for the PIM1-1 complex to improve the potency and selectivity. This approach afforded the potent and metabolically stable PIM1-selective inhibitor 14, which shows only a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 72 publications
5
58
0
Order By: Relevance
“…Moreover, in cancer patients, upregulation of Pim-3 expression level is significantly correlated with the FIGO stage (p<0.05), histopathological subtypes (p<0.05) and metastasis (p<0.05). Recently, several studies reported that Pim-3 could promote cancer invasion and metastasis in gastric and pancreatic cancer, sarcoma and other tumors (Nakano et al, 2012;Zhang et al, 2013;Lou et al, 2014). These findings regarding the role of Pim-3 in different cancers support the clinical results of our study, implying that Pim-3 may ubiquitously promote cancer invasion and metastasis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, in cancer patients, upregulation of Pim-3 expression level is significantly correlated with the FIGO stage (p<0.05), histopathological subtypes (p<0.05) and metastasis (p<0.05). Recently, several studies reported that Pim-3 could promote cancer invasion and metastasis in gastric and pancreatic cancer, sarcoma and other tumors (Nakano et al, 2012;Zhang et al, 2013;Lou et al, 2014). These findings regarding the role of Pim-3 in different cancers support the clinical results of our study, implying that Pim-3 may ubiquitously promote cancer invasion and metastasis.…”
Section: Discussionsupporting
confidence: 89%
“…And Pim-3 was also associated with sarcoma-induced bone invasion (NarlikGrassow et al, 2012). The inhibition of Pim-3 by shRNA also reduced endothelial cell spreading, vascular tube formation, and migration of prostate cancer (Nakano et al, 2012). Pim-3 can be regulated by the Ets family of transcription factors in NIH3T3 cells and human Ewing's sarcoma cells (Deneen et al, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…We believe that inhibitors such as compound 1 (Fig. 3a) and its derivatives described in Nakano et al (2012) have the potential to be developed further. Compound 14, the most advanced of the series, inhibits the growth of the human leukaemia cell line MV4-11 (Nakano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…3a) and its derivatives described in Nakano et al (2012) have the potential to be developed further. Compound 14, the most advanced of the series, inhibits the growth of the human leukaemia cell line MV4-11 (Nakano et al, 2012). Like compound 1 and its derivatives, binding of 14 caused the P-loop to adopt a novel conformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation